MANAJEMEN PARENTING BERBASIS BUDAYA LOKAL CIREBON - saifuddin saifuddin (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2021)
Parenting education provides knowledge to parents to educate their children, parents as the front guard in educating children must acquire knowledge of how, what and why parenting education must be obtained by parents. This education can be done by parents by consulting with educational institutions, in this research RA educational institutions in Cirebon district in case studies in RA Baiturridwan Gebang and RA Tholaal Badr Gunung Jati. This study uses a qualitative method with a naturalistic approach in observation and data collection, and the researchers themselves in this study as the main instrument. The research discussion is divided into three aspects, namely: first, the parenting aspect is an important aspect for providing education to children, this parenting can be said to be a parent who plays a major role in creating education based on local wisdom. both aspects of educating children are an important part of education. The three Cirebon local cultures are important aspects that must be considered by all parties, especially parents and teachers, parents at the teacher's house when at school. The researcher concludes this study, as follows: In the aspect of educating children, many parents do not understand how to provide education to their children, especially when they gather together with their families and even do not find the time agreed by the family. In the aspect of Cirebon's local culture, many families do not use the free language. In the parenting aspect, parents do not carry out education in order to improve their quality to get parenting knowledge, they tend to ignore, In the parenting aspect as an evaluation, parents should be fully involved to become the front teachers in the home.